A Psycholinguistic Approach to Enhancing Arabic Vocabulary and Morphology Mastery Through Inspirational Quotes - Habib, Moh. Tohiri; Masnun, Masnun; Mahmudah, Menik; Syakur, Sultan Abdus (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study investigates the effectiveness of using inspirational Arabic quotes to enhance vocabulary acquisition and morphological understanding among Arabic language learners. Employing a three-week mixed-methods design that integrated both qualitative and quantitative data, the research involved 30 students aged 16-18 from Pondok Pesantren Darullughah Wadda’wah engaged with Arabic quotes to enrich vocabulary and morphological skills. Pre and post-assessments revealed significant improvements in vocabulary retention, morphological awareness, and contextual vocabulary usage. The psycholinguistic elements embedded in inspirational quotes served as mnemonic devices, facilitating deeper engagement and motivation among students. Findings suggest that inspirational quotes bolster vocabulary acquisition and promote cultural resonance and emotional engagement, making Arabic language learning more effective and meaningful. This approach, encapsulated in the acronym EMPOWER—Engagement, Motivation, Practice, Optimised Learning, Wisdom Integration, Emotional Resonance, and Retention—presents a holistic model for Arabic language education, emphasising motivational and cultural learning contexts to enhance language proficiency.